METODE IJTIHAD IMAM ABU HANIFAH DAN IMAM MALIK - Irwansyahlubis; Halimatus Adiah; Muhammad Sibawaih (LPPM-IAI BATAM, 2022)
Along with the times and technology. As well as the increasingly rapid socio-cultural changes that are increasingly complex on all fronts. So it has major implications for Islamic law in this world. This is marked by the many problems that arise in the midst of the Islamic community. Some of the problems that arise still require ijtihad formulas to determine their legal status. Meanwhile, the Messenger of Allah is no longer there, and the revelation has also been sent down. To find the formulation of Islamic law on issues that have not been determined by law in the Qur'an and hadith. And it is not found in the ijtihad fatwas of contemporary scholars. Then came the ijtihad. As one of the methods used by mujtahid scholars in formulating these contemporary Islamic legal issues. And this method of ijtihad had been carried out during the time of the Prophet and during the time of the Prophet's companions. And the more complex the problem is, the more competent scholars are born who have the competence to perform ijtihad. Among them are Imam Hanafi and Imam Malik. And after being examined, each of these scholars has quite a different model of ijtihad. Imam Abu Hanifah based his thoughts and models of ijtihad on the Koran, sunnah, ijma', qiyas, and istihsan. While Imam Maliki in developing ijtihad, is guided by several sources, namely the Koran, sunnah, ijma', qiyas, qaul shahabi, madinah expert charity, mashalih mursalah, istishab, syaddudz dzari'ah, and syar'u man qablana.